If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12m^2+17m=0
a = 12; b = 17; c = 0;
Δ = b2-4ac
Δ = 172-4·12·0
Δ = 289
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{289}=17$$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(17)-17}{2*12}=\frac{-34}{24} =-1+5/12 $$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(17)+17}{2*12}=\frac{0}{24} =0 $
| 11x-3=9+5 | | X+6/5-x-6/49=1 | | 6x^2-11x^2-6x=0 | | 3=4x+6 | | 5b+7=–3b | | 3p-5=4p+10 | | y(2y^2-21y-11)=0 | | 8y-16y=42-54 | | n/15-10=-11 | | 16x2+72x+81=0 | | X+7=5x-2 | | 0.16(x-5)=0.5(x+6) | | 200=-0.5x^2+100x-60 | | -x-7+5=-8x-23 | | -31/2(n-1)=49/5 | | 2/y=8/20 | | 3+(n+2)=15 | | −0.5x+1=7x−14 | | 7-2(x-6)=5-(2x-4) | | -2(x+1)=2(x-1 | | 1+2x-4=-3-(x) | | 6(1-7x)-3x=-3x+6 | | 5x-3*5=x+4x-12 | | 7-2(x-6)=5-(x-4) | | 9x^2+7x+70=0 | | j+50J=0 | | -3c-10=-22 | | 4b+6b=0 | | (6x^2-5)^1/4=x | | -24+5x=4(2×-6) | | 2(3x-9)=3x+1 | | X+6/5=x+6/49=1 |